'Ephemeral vs eternal’: Modi's comments cross the Belur Math's Laxman Rekha - Kanungo, Pralay (The wire, 2020)
The prime minister found out that the Ramakrishna Mission will not be willing to entertain opulence, arrogance and transgression by anyone, howsoever powerful he may be.